Evaluation of fungicides for the control of powdery mildew disease in coriander (Coriandrum sativum L.) - Singh, A K (Journal of Spices and Aromatic Crops, 2006)
Six fungicides were evaluated at Raigarh (Chhattisgarh), for the control of powdery mildewdisease of coriander (Coriandrum sativum), caused by Erysiphe polygoni. All the fungicides re-duced the disease severity significantly, over control, with maximum reduction inhexaconazole (0.1%) that was on par with propiconazole (0.1%) and wettable sulfur (0.3%).Yield of coriander was higher 2.54, 2.00 and 2.20 times, over control, in hexaconazole (0.1%),propiconazole (0.1%) and wettable sulfur (0.3%), respectively. Cost-benefit ratio was 1:5.3,1:4.0 and 1:4.5 in hexaconazole (0.1%), propiconazole (0.1%) and wettable sulfur (0.3%),respectively.